(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Rapidly developing science and technology has made it possible to use new tools, equipment and facilities in the field of education and personnel training. Among these, computers are undoubtedly the most prominent. Research shows that this new technology has a positive effect on attracting students’ attention, facilitating learning and increasing their motivation. However, due to the lack of programs in the field, there is a huge gap in the application of these technological capabilities in our country. This study aims to contribute to filling this gap and experimentally support a new curriculum that includes - to support modern physical sciences at the middle and high school level; Newly developed Simulation programs and Interactive screen experiences in the computer environment have been introduced. These programs are thought to contribute greatly to concretizing abstract topics and making them more comprehensible in an introduction to modern physics. In addition, the fact that many secondary educational institutions in our country are still not conducting these experiments due to financial reasons increases the importance of the newly developed programs.